Effects of the Three Teaching Strategies on the Performance in Mathematics of Grade V Pupils of Ampayon Central Elementary School, Butuan City Division - Gregorio, Sandra O. (Randwick International of Education and Linguistics Science Journal, 2025)
This study examined the effects of three teaching strategies—multisensory, think-pair-share, and lecture method—on the mathematics performance of Grade V pupils at Ampayon Central Elementary School, Butuan City Division. Employing a quasi-experimental design with three groups of 40 pupils each, the research utilized pretests and posttests based on the K–12 Basic Education Curriculum in Mathematics. Data were analyzed using Analysis of Covariance (ANCOVA). Findings revealed significant differences in performance across the strategies, with the multisensory approach producing the highest mean scores, followed by think-pair-share, while the lecture method yielded the lowest. Pupils exposed to multisensory and think-pair-share strategies demonstrated greater interest, higher engagement, and more substantial learning gains compared to the traditional lecture-discussion group. The study concludes that the multisensory approach is the most effective strategy for enhancing mathematics learning outcomes. It recommends that teachers and school leaders adopt varied pedagogical approaches to foster improved student performance and to align with the goals of the Department of Education in promoting quality instruction.